2005
DOI: 10.1136/jme.2004.010280
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of women’s views on medical confidentiality

Abstract: Context:The need to reinvigorate medical confidentiality protections is recognised as an important objective in building patient trust necessary for successful health outcomes. Little is known about patient understanding and expectations from medical confidentiality.Objective:To identify and describe patient views of medical confidentiality and to assess provisionally the range of these views.Design:Qualitative study using indepth, open ended face-to-face interviews.Setting:Southeastern Pennsylvania and southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
0
15
0
6
Order By: Relevance
“…Pacientų pasitikėjimas gydytojais ir apskritai medicinos darbuotojais yra abipusių sėkmingų santykių prielaida (3)(4)(5)(6). Pacientų pasitikėjimas medicinos darbuotojais turi įtakos jų pasitenkinimui gydymu ir gydymo rezultatais (7).…”
Section: įVadasunclassified
See 2 more Smart Citations
“…Pacientų pasitikėjimas gydytojais ir apskritai medicinos darbuotojais yra abipusių sėkmingų santykių prielaida (3)(4)(5)(6). Pacientų pasitikėjimas medicinos darbuotojais turi įtakos jų pasitenkinimui gydymu ir gydymo rezultatais (7).…”
Section: įVadasunclassified
“…nuo pasitikėjimo, tarpusavio pagarbos ir konfidencialumo užtikrinimo mokslinėje literatūroje skiriama pakankamai daug dėmesio. Daugumoje straipsnių konfidencialumo problema nagrinėjama pirminės sveikatos priežiūros lygmeniu (3)(4)(5)(6)(7)(8)18) ir sprendžiant problemas, susijusias su įvairiomis ligomis: psichikos, AIDS (19), užkrečiamomis ar kitomis ligomis (20), taip pat suteikiant paliatyviąją pagalbą (23). Nemažas dėmesys skiriamas paauglių problemoms (21,22).…”
Section: Pav Pacientų Ir Gydytojų Nuomonės Palyginimas Atsakant į Klunclassified
See 1 more Smart Citation
“…The technique of Multilevel Consensus Coding was used to identify themes and refine the conceptual model. 31 Each transcript was read by at least 3 of the study investigators, each of whom identified major themes and subthemes. Investigator meetings were used to review these themes and subthemes and resolve differences in coding or interpretation.…”
Section: Methodsmentioning
confidence: 99%
“…If this group could not resolve the problem, the passage was omitted from analysis. This method, termed multilevel consensus coding, was developed by the authors, has been applied in multiple settings, 40,41 and meets accepted standards of validity in qualitative research. 42,43 This article reports data from the section of the interview that focused on respondents' understanding of the cause of their condition.…”
Section: Codingmentioning
confidence: 99%